2020
DOI: 10.1088/2053-1591/ab5f6d
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed antiferromagnetic ordering and enhanced electrical conduction in doped iridate Sr2−xPrxIrO4

Abstract: Sr 2 IrO 4 has been shown to exhibit a novel J eff =1/2 Mott spin-orbit insulating state with antiferromagnetic ordering. In the present investigation, the effects of Pr substitution at Sr-site on structural, magnetic and electrical properties are studied in Sr 2 IrO 4 . Pr-doped samples still retain the insulating behavior, but with the increase of Pr doping concentration, the resistivity decreases. The magnetic properties show that long-range antiferromagnetic order is collapsed when the Pr doping content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…. The transport behaviors divided by three temperature ranges have also been observed in previous reports [13,14]. All the fitted data are shown in Table 3.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…. The transport behaviors divided by three temperature ranges have also been observed in previous reports [13,14]. All the fitted data are shown in Table 3.…”
Section: Introductionsupporting
confidence: 67%
“…One possible method to induce a metal from a Mott insulator is to substitute the Sr or Ir elements via chemical doping [8]. For example, A slight doping at either the Ir 4+ site (e.g., Rh 3+ , Ru 4+ , Tb 4+ , Cu 2+ , V 4+ , Ga 3+ , Sn 4+ , and Ti 4+ , Co 4+ , Fe 3+ [6][7][8][9][10][11]) or the Sr 2+ site (e.g., La 3+ , Pr 3+ , Sm 3+ , Ga 3+ , Ca 2+ , K + and Eu 3+ [12][13][14][15][16]) brings about large variations in either the electric transport property or the magnetic property or both. However, the properties of Sr 2 IrO 4 are extremely sensitive to chemical doping.…”
Section: Introductionmentioning
confidence: 99%
“…What is more interesting is that another λ-like feature appears at low temperature region ( 15 K) of the M ∼ T curves in the 0.06 x 0.2 samples. To our best knowledge, no previous literature have reported this low temperature λ-like feature in undoped or doped Sr 2 IrO 4 systems [21][22][23][24][26][27][28][29]. Thus it is suggested that this feature is originated from the magnetism of Mn ions.…”
Section: Resultsmentioning
confidence: 93%
“…For examples, a lot of rare earth elements have been chosen to dope at the Sr site of Sr 2 IrO 4 . In spite of a few reports of insulating-to-metal transition in doped single crystals, in most cases, the Sr 2−x RE x IrO 4 (RE = rare earth elements) polycrystalline samples exhibit insulating behaviors at low temperatures [21][22][23][24]. Besides, a recent work reports a persistent insulating state of Sr 2 IrO 4 upon application of pressure up to megabar [25].…”
Section: Introductionmentioning
confidence: 99%